Ответы и объяснения

2013-04-17T17:52:18+00:00

(x2.9)+(x1.3-2.3)=366.08

x4.2-2.3=366.08

x4.2=366.08+2.3

x4.2=368.38

x=368.38:4.2

x=3683.8:42

x=87,7095238095

Ответ:x=87,7095238095

2013-04-17T18:14:40+00:00

Выражение: x2.9+x1.3-2.3=366.08

Ответ: x2.9+x1.3-368.38=0

Решаем по действиям:
1. -2.3-366.08=-368.38
  +366.08
   _ _ _2_._3_0_
   368.38

Решаем по шагам:
1. x2.9+x1.3-368.38=0
  1.1. -2.3-366.08=-368.38
      +366.08
       _ _ _2_._3_0_
       368.38


Решаем уравнение x2.9+x1.3-368.38=0: